Adenoviral associated gizzard erosions: an overview and case example. (2nd July 2022) - Chapman, Esme; Hersey, William
Abstract : Adenoviruses are of increasing concern in both human and veterinary medicine. The effects of adenoviruses in poultry species have been well documented for many decades. Adenoviral gizzard erosion (AGE) is one such syndrome that affects chickens and is caused by members of group A of the fowl adenoviruses. Development of clinical AGE is poorly understood, but cases of this syndrome can lead to economic losses and welfare concerns in both broiler and layer populations. Clinical signs, gross post-mortem lesions and histological lesions can all be used to help identify cases of AGE in practice. This article will explore AGE in the context of clinical poultry practice, including an overview of the aetiology, transmission, clinical signs, diagnosis and control of AGE.